Validation of plasmasphere electron density reconstructions derived from data on board CHAMP by IMAGE/RPI data. Issue 1 (1st January 2015) - Gerzen, T.; Feltens, J.; Jakowski, N.; Galkin, I.; Denton, R.; Reinisch, B.; Zandbergen, R.
Abstract: Plasmaspheric electron content is, beyond the ionosphere as major source, a significant contributor to the overall TEC budget affecting GNSS signals. The plasmasphere can induce half or more of the GNSS range errors caused by atmospheric electrical charges, in particular at nighttime. At DLR Neustrelitz, Germany, GPS measurements recorded onboard the LEO satellite CHAMP were used to reconstruct the topside electron density distribution (ionosphere and plasmasphere) up to GPS altitude, applying a model-based assimilation technique. In this paper, the potential of these CHAMP topside reconstructions for analyzing space weather related changes in the geo-plasma is investigated. For this purpose, comparisons are made between the CHAMP reconstructed profiles and electron densities derived from passive radio wave observations by the IMAGE RPI instrument for years 2001 till 2005. The comparison results indicate that an improvement, compared to the electron density of a background model, can be achieved by CHAMP data assimilation. The improvement is especially visible in the L -shell region below 3, which contributes notably to the GNSS signal delays. However, for the region around the plasmapause, systematical electron density underestimations of the background model w.r.t. the IMAGE data are detected. The rather limited CHAMP data coverage and the degraded observation geometry at these high altitudes seem to be not sufficient for complete compensation of this underestimation during the assimilation procedure. The results presented in this paper demonstrate the strengths of LEO TEC data assimilation, but at the same time illustrate the necessity to improve the modeling of the plasmasphere region above 4 ER L -shell distances. Furthermore, they reveal the need of additional data to establish an appropriate data base for the modeling of the complete plasmasphere.